Alzheimer's polygenic risk score in general population reveals new biomarkers for early diagnosis: Genetics: Genetics of cognitive aging, other dementia, and endophenotypes. (7th December 2020) - Karkar, Slim; Philippe, Cathy; Hager, Alexa; Mangin, Jean‐Francois; Frouin, Vincent
Abstract: Background: In aging population, Alzheimer's disease (AD) with its different stages (preclinical, prodromal, mild to severe) has a strong genetic component. For a given individual and using summary statistics available from powerful reference GWAS in Alzheimer's disease (IGAP, Lambert, 2013), one can compute a Polygenic Risk Score (PRS) for AD, that is a cumulative genetic risk computed with one subject's genome variants. Using individual's PRS and MRI images in an aging general population like UK Biobank, we could point at imaging markers (endophenotypes) associated with early stages of AD. Method: 16, 549 subjects aged 47‐74 from UK Biobank were included in the analysis. Using anatomical T1 MRI images (3T), opening measurements in 123 sulci were extracted with BrainVisa/Morphologist pipeline. Individual's PRS were computed using PRSice and summary statistics from IGAP study and then have been tested for an association with sulcal opening measurements. Result: We obtained 24 sulci for which opening measurements was either positively or negatively associated with PRS (p < 0.05 after FDR correction). 17 sulcal opening showed increased widening w.r.t PRS with a main focus around the precuneus region, with superior parietal and central sulci. 7 sulcal opening showed opposite effect w.r.t the PRS and are located mostly in the orbital and insula region. See Figure for details. Conclusion: For neurological disease like AD that have a strong genetic background, the combination of genetics and imaging data in large, aging general population studies like UK Biobank, provides powerful tools to identify new possible early markers of neurodegeneration. Focus on early risk patterns as the ones presented here with a main result on parietal sulcal alterations might facilitate identification of individuals at risk for cognitive decline and possibly support diagnostic procedures for AD.